Determination and uncertainty analysis of inorganic arsenic in rice by UHPLC-ICPMS - Rangasamy, Rajesh; Malekadi, Praveen Kumar; Mohamed, D. Peer; Tyagi, Dheeraj Kumar; Raveendran, Rahul; Gupta, Ananda (Acta Biologica Szegediensis, 2021)
The present study arose from the need of to determine inorganic arsenic (iAs) at low levels in rice. Ultra-high performance liquid chromatography coupled with inductively coupled plasma mass spectrometry (UHPLC-ICPMS) using Kinetic Energy Discrimination (KED) mode to eliminate spectral interferences was used for analysis of iAs. Sample preparation involves extraction of inorganic arsenic (sum of As3+ and As5+) with water by heating at 90 °C for 5 min in water bath. Separation is accomplished with a reversed-phase ion pack column using a gradient chromatographic method followed by ICPMS analysis within 5 min. The method was validated in accordance with Commission Regulation (EU) No 836/2011 and performance characteristics were verified. Acceptable values were obtained for specificity, repeatability (HorRatr < 0.6), within-lab reproducibility (HorRatR < 0.3) with recovery 80-90%, limit of quantification (0.02 mg/kg), fitness-for-purpose and trueness (using CRM); thus, the method can be considered for oﬃcial control purposes.